Measurement of J/ψ production cross-sections in pp collisions at s $$ \sqrt{s} $$ = 5 TeV - The LHCb collaboration (SpringerOpen, 2021)
Abstract The production cross-sections of J/ψ mesons in proton-proton collisions at a centre-of-mass energy of s $$ \sqrt{s} $$ = 5 TeV are measured using a data sample corresponding to an integrated luminosity of 9.13 ± 0.18 pb −1, collected by the LHCb experiment. The cross-sections are measured differentially as a function of transverse momentum, p T, and rapidity, y, and separately for J/ψ mesons produced promptly and from beauty hadron decays (nonprompt). With the assumption of unpolarised J/ψ mesons, the production cross-sections integrated over the kinematic range 0 < p T < 20 GeV/c and 2.0 < y < 4.5 are σ prompt J / ψ = 8.154 ± 0.010 ± 0.283 μb , σ nonprompt J / ψ = 0.820 ± 0.003 ± 0.034 μb , $$ {\displaystyle \begin{array}{c}{\sigma}_{\mathrm{prompt}}\ J/\psi =8.154\pm 0.010\pm 0.283\ \upmu \mathrm{b},\\ {}{\sigma}_{\mathrm{nonprompt}}\ J/\psi =0.820\pm 0.003\pm 0.034\ \upmu \mathrm{b},\end{array}} $$ where the first uncertainties are statistical and the second systematic. These cross-sections are compared with those at s $$ \sqrt{s} $$ = 8 TeV and 13 TeV, and are used to update the measurement of the nuclear modification factor in proton-lead collisions for J/ψ mesons at a centre-of-mass energy per nucleon pair of s NN $$ \sqrt{s_{\mathrm{NN}}} $$ = 5 TeV. The results are compared with theoretical predictions.